Training Effectiveness and Job Satisfaction: The Role of Organizational Support and Employee Tenure in Boutique Hotels - Sugiarto, Yayan; Puri, Raden Intan Media Ratna; Fitriani, Dewi (Politeknik Negeri Bandung, 2025)
The hospitality sector in West Java, particularly boutique hotels, faces ongoing challenges in sustaining employee satisfaction and service quality in an increasingly competitive environment. This study explores the relationship between training effectiveness, perceived organizational support (POS), and service job satisfaction, with employee tenure as a moderating variable. Data were collected from 120 front-line hotel staff and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings indicate that training effectiveness positively influences both POS and job satisfaction, with POS mediating the relationship. Employee tenure moderates these effects, suggesting that satisfaction outcomes vary across different career stages. The study contributes to the Social Exchange Theory by integrating tenure as a conditional factor that shapes the dynamics of training and support in service-oriented organizations.